TIBBIYOT OLIYGOHI TALABALARIGA MIKROBIOLOGIYA,VIRUSOLOGIYA,IMMUNOLOGIYA FANINI O’QITISHDAGI ZAMONAVIY PEDAGOGIK TEXNOLOGIYALAR (Modern education and development, 2025)
This article presents the types of modern pedagogical technologies in the teaching of microbiology, virology, and immunology at the present day and at the stage of development of the science, their differences and the teaching methods of the superior ones are highlighted. Conclusions about which one is more effective to use given.